Who does the norm affect? Information design from a feminist perspective - Novais Queiroz, Bianca; Tiradentes Souto, Virginia (InfoDesign, 2024)
A huge and growing amount of data is omnipresent in our daily lives. To make sense of the information overload, data visualisation and infographics are used as cognitive artefacts. The design of these solutions, in turn, is usually mediated by a set of guidelines that set parameters for what is considered good design. The norm thus suggests a collective commitment to design and involves the expression of the values of the dominant group that designed it. This study explores normative biases and presents counter-positions to the sovereignty of these hegemonic values in information design from a critical feminist perspective. It is noteworthy that during the period analysed, intellectual recognition was mainly given to men. The complexity of male protagonism in the production of knowledge is addressed. The shift away from the primacy of the influences of a dominant group therefore represents a redistribution of power that benefits not only women but also various social groups.